La nueva organización del trabajo en los proveedores directos en Catalu\~na de los fabricantes de automóviles - F. Llorente Galera (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2007)
This paper analyses the introduction of new work organisation in Catalonian direct suppliers firms of OEM, specially the lean production labour practices. We check on a sample of firms that although some new lean production labour practices have been effectively introduced, they require further integration. We identify three typology firms about their labour organization, using cluster analysis with results of Homals, wich haven't significant differences for ratios of productivity, ROS and ROA.
Keywords: 330; automotive; labour organization; suppliers; typologies; Catalonia